Clinicopathologic factors predicting lymph node metastasis in superficial esophageal squamous cell carcinoma. (May 2014) - Moon, Jung Youn; Kim, Gwang Ha; Kim, Ji Hyun; Kim, Hyung Hun; Ryu, Kwang Duck; Park, Seong Oh; Lee, Bong Eun; Song, Geun Am
Abstract Objective. Surgical resection is the treatment of choice for superficial esophageal squamous cell carcinoma (SESCC), but it is associated with high mortality and morbidity rates. Recently, endoscopic resection for SESCC has been indicated for patients with a low risk of lymph node metastasis (LNM). Therefore, to successfully treat SESCC with endoscopic resection, it is very important to identify patients with a low risk for LNM. The objective of this study was to investigate clinicopathologic factors that predict LNM in patients who underwent esophagectomy for SESCC. Methods. The study included 104 patients with SESCC from three university hospitals in Pusan, Korea. Clinicopathologic factors were evaluated to identify independent factors predicting LNM by univariate and multivariate analyses. Results. In univariate analysis, the depth of tumor invasion and lymphovascular invasion had significant influences on LNM (p = 0.001 and p < 0.001, respectively). Gross type, tumor size, and tumor differentiation were not predictive for LNM. In multivariate analysis, the depth of tumor invasion and lymphovascular invasion were signiﬁcantly associated with LNM in patients with SESCC (OR 9.04, p = 0.049; OR 11.61, p = 0.002, respectively). Conclusions. The depth of tumor invasion and lymphovascular invasion were independent predictors of LNM in patients with SESCC. Therefore, endoscopic resection could be performed in patients with SESCC that is limited to the mucosa, without lymphovascular invasion.